Serum Amyloid A Promotes Invasion of Feline Mammary Carcinoma Cells - TAMAMOTO, Takashi (The Japanese Society of Veterinary Science, 2014)
The serum amyloid A (SAA) concentration is higher in mammary tumors with metastases in both humans and animals. In the present study, the direct effects of recombinant feline SAA (rfSAA) protein on invasiveness of feline mammary carcinoma cells were evaluated. As an indicator of invasiveness, matrix metalloproteinase-9 (MMP-9) expression was investigated in 4 feline mammary carcinoma cell lines of different origins. In 3 of 4 cell lines, MMP-9 expression was significantly increased by rfSAA stimulation. The invasive capacities of feline mammary carcinoma cells were also stimulated by rfSAA. The findings of this study have identified a novel role for SAA in mammary tumorigenesis and suggest that therapeutic strategies targeting SAA may provide new alternatives in treating tumor invasion and metastasis.